Geometric Modeling of Sheet Deformation within a Virtual Environment - Mahal, B.S.; Clark, D.E.R.; Simmons, J.E.L. (International Journal of Virtual Reality, 2001)
In this paper we present a real-time, computationally inexpensive environment for on-screen, accurate simulations of thermoplastic sheet materials on a conventional Personal Computer. A pseudoimmersive virtual environment is constructed to handle the implementation of a real-time aesthetically accurate deformation algorithm called MaSSE: Mass-Spring Simulation Engine. The motion of the sheet is controlled by gravity and by using a mouse-pointing device to manipulate the sheet within the environment. An application for the environment is centered on, although not restricted to, mechanical engineering-based real-time simulations of heat-sensitive sheet materials.